Evaluation of native acidophilic algae species as potential indicators of polycyclic aromatic hydrocarbon (PAH) soil contamination - Diaz, Monica Mabel (2015)
Polycyclic aromatic hydrocarbons (PAHs) are pollutants that are potentially carcinogenic, are widely distributed in the environment, and accumulate in soils. The peroxydisulfate anion strategy for the remediation of PAH-contaminated soils has attracted widespread interest, despite its negative effects on soil microbial activity as a result of oxidative stress and a decrease in pH of the soil caused by the treatment. The acidification caused by the process can itself affect the growth of the normal flora, regardless of the presence of PAHs. For this reason, it is necessary to identify microorganisms that are capable of developing in acidic environments and are sensitive to the presence of PAHs. The objective of the present study was to identify native acidophilic/acid-tolerant algae isolated from the Agrio River-Lake Caviahue system, Argentina, that could possibly be used as bioindicators of soil PAH contamination. Two of the three acidophilic species assayed were identified as potential bioindicator species. Cyanidium caldarium and Euglena mutabilis were responsive to PAH contamination in the tested soils, while the response of Keratococcus rhaphidioides was dependent on the type of soil. The use of acidophilic and cosmopolitan species, such as C. caldarium and E. mutabilis, as bioindicators is a promising first step for assays of PAH contamination in soils.